Impact of Different Management Systems on Biodiversity Conservation: a Case Study - Sahoo, T. K.; Mishra, T. K.; Jain, Avinash; Banerjee, S. K. (Indian Forester, 2004)
In the present communication , the impact of different management systems on biodiversity conservation in Abhoya of Midnapore District of West Bengal (India) has been assessed. Vegetation survey of plant communities and distribution pattern were conducted through Important Value Index (IVI) in three types of forest communities , such as FPC-managed forest , plantation stand (1960) managed by State Forest Depari:ment and degraded forest. These surveys covered four major seasons viz. summer , monsoon , post-monsoon and winter in this region. Maximum number of species were observed during post-monsoon and in FPCmanaged forest. The coppice Sal forest , which is the predominant natural forest type of this region , S. robusta has become the dominant tree with-varying IVI in different communities. Herbaceous species were found to be more adapted to a developing community like coppice Sal forests than a plantation stand or a degraded forest. Comparing different phytosociological parameters , FPC-managed forests were found to have more diversity in species structure irrespective of seasonal variations , whereas in plantation stand and degraded forest the species diversity becomes lower. The concentration of dominance was observed inversely proportional with species diversity. Highest evenness index was calculated maximum for FPC-managed forests and during post-monsoon or monsoon. Species richness index did not differ significantly among three communities and in four seasons. Based on IVI values the abstract community in Abhoya was identified as Shorea-Holarrhena-Eragrostis. The study indicates that involvement of forest fringe people in protecting the forest through JFM can increase the forest cover. It is better to study the phytosociological characters in post monsoon period.